Biomass Sorghum: Effect of Acid, Basic and Alkaline Peroxide Pretreatments on the Enzymatic Hydrolysis and Ethanol Production - Santos,Beatriz Vieira dos (2021)
Abstract This study evaluated the effects of three chemical pretreatments of biomass sorghum (BS): dilute alkaline (PTA1 and PTA2), dilute acid (PTB1 and PTB2) and alkaline hydrogen peroxide (PTC1 and PTC2) in the enzymatic hydrolysis and ethanol production. Among the six investigated conditions, the pretreatment with 7.36% H2O2 (PTC2) was the most efficient in the lignin removal and preservation of the polysaccharide fraction. After the enzymatic hydrolysis, increases in the glucose and xylose concentrations were observed in the pretreated BS hydrolysates, mainly in PTB1 and PTC1. All the hydrolysates obtained low concentrations of inhibitors. In the alcoholic fermentations with Pichia stiptis, the greatest ethanol yield was obtained in PTB1 hydrolysate (3.84 g L-1), corresponding to 16.15% of yield. The highest ethanol yield in PTB1 hydrolysate can be justified by the maximum concentration of xylose obtained in this hydrolysate, demonstrating the potential of P. stiptis in the fermentation of pentose to ethanol. The results indicated that biomass sorghum is an alternative lignocellulose source with potential for the production of second generation ethanol, opening up prospects for additional studies.